(untitled) (Bangladesh Journal of Child Health, 2010)
Background and Objectives: Diagnosis of perinatal asphyxia is mostly established retrospectively. But it is difficult to diagnose perinatal asphyxia retrospectively in the absence of perinatal records. As because of hypoxaemia, different organ systems of the body are affected in perinatal asphyxia, this study was done to assess the hepatic function for the diagnosis of perinatal asphyxia and to find out any correlation existing between hepatic enzyme change and the severity of perinatal asphyxia. Methods: A total of 70 full-term asphyxiated newborns (study group) were studied during January 2008 to December 2008 in the department of Paediatrics, Mymensingh Medical College Hospital. After enrolment these babies were grouped according to Sarnat and Sarnat stages of HIE as stage I, II and III. Another 50 healthy newborns were also studied as reference group. Venous blood was analyzed between 2nd and 5th day of life to estimate serum AST, ALT and alkaline phosphatase (ALP), serum total bilirubin (STB), serum total protein (STP), serum albumin and prothrombin time (PT). Unpaired student’s ’t’ test and Spearman’s rank correlation was used for data analysis and P value of <0.05 were considered significant. Results: The mean AST, ALT, ALP, STP, S. albumin and TSB of asphyxiated babies were 76.3±37.4 U/L, 82.2±48.08 U/L, 369.6±123.05 U/L, 55.7±8.8 U/L, 32.6±5.5 g/L & 5.5±2.01mg/dL respectively and those of normal babies were 23.5±8.5 U/L, 26.5±7.8 U/L, 208.2±46.9 U/L, 66.3±10.4 g/L, 40.9±6.5 g/L and 4.5±1.2 mg/dl respectively and these differences were statistically significant (P <0.001). On the other hand no significant changes were noted in prothrombin time. The rise of AST, ALT, ALP and PT also showed a significant positive correlation with the severity of asphyxia and the stages of HIE. Conclusion: It is concluded that estimation of hepatic enzymes can be used to diagnose perinatal asphyxia and also to assess its severity. Key words: Alanine aminotransferase; aspartate aminotransferase; newborn; perinatal asphyxia. DOI: 10.3329/bjch.v34i1.5695 Bangladesh Journal of Child Health 2010; Vol.34(1): 7-10